Boardroom matter unveiled: navigating expertise, education, gender, and corporate reputation in Malaysia / Elinda Esa ... [et al.] - Esa, Elinda; Mohamad, Nor Raihan; Wan Zakaria, Wan Zuriati; Illias, Nor Azlina (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
In the bustling corridors of corporate Malaysia, the boardroom emerges as a symphony of strategic decision-making, where its members’ expertise, educational backgrounds, and gender intricately weave the narrative of a company’s reputation. This study delves into the nuanced connection between boardroom expertise, educational backgrounds, and board gender, exploring their symbiotic role in shaping the reputational tapestry of Malaysian publicly listed companies using the new proxy for reputation. Earlier research indicated that the composition of boards can reliably predict a company’s strong reputation. However, there is a notable scarcity of evidence regarding how these variables influence the novel approach to measuring reputation. This becomes especially pertinent when considering the transparency of corporate reputations in developing countries such as Malaysia. The present investigation gathered secondary data from company annual reports spanning 2017 to 2020, employing content analysis over this four-year period. A self-designed checklist for corporate reputation was utilized for measurement. The findings have shown that board expertise, board education, and board gender significantly influence a company’s reputation. The results furnish valuable support and evidence for companies in Malaysia and other developing nations, emphasizing the importance of incorporating more educated, experienced, and female directors into their strategies for effective reputation management.